Finding the niche: A review of market assessment methodologies for rural electrification with small scale wind power. (November 2020) - Leary, J.; Czyrnek-Delêtre, M.; Alsop, A.; Eales, A.; Marandin, L.; Org, M.; Craig, M.; Ortiz, W.; Casillas, C.; Persson, J.; Dienst, C.; Brown, E.; et al.
Abstract: The mass roll out of solar PV across the Global South has enabled electricity access for millions of people. In the right context, Small Wind Turbines (SWTs) can be complementary, offering the potential to generate at times of low solar resource (night, monsoon season, winter, etc.) and increasing the proportion of the total energy system that can be manufactured locally. However, many contextual factors critically affect the viability of the technology, such as the extreme variability in the wind resource itself and the local availability of technical support. Therefore, performing a detailed market analysis in each new context is much more important. The Wind Empowerment Market Assessment Methodology (WEMAM) is a multi-scalar, transdisciplinary methodology for identifying the niche contexts where small wind can make a valuable contribution to rural electrification. This paper aims to inform the development of WEMAM with a critical review of existing market assessment methodologies. By breaking down WEMAM into its component parts, reflecting upon its practical applications to date and drawing upon insights from the literature, opportunities where it could continue to evolve are highlighted. Key opportunities include shifting the focus towards development outcomes; creating community archetypes; localised studies in high potential regions; scenario modelling and MCDA ranking of proposed interventions; participatory market mapping; and applying socio-technical transitions theory to understand how the small wind niche can break through into the mainstream. Highlights: Small scale wind power requires a detailed market assessment. WEMAM is a multi-scalar, transdisciplinary methodology designed for small wind. A review of market assessment literature highlights new techniques. Reflections on the implementations of WEMAM to date guide its evolution.